The contribution of 21st century pastoralists to biodiversity conservation and emerging bioeconomies - French, K (Society of Ethnobiology, 2017)
Anatomically modern humans (AMH, Homo sapiens) have only bred and managed livestock for 10,000 years, yet these activities have led to profound global ecological and cultural changes that are still felt today. Pastoralism is the practice of raising domesticated animals for food and fiber and takes many forms depending on geographic location. Some pastoralists (also known as herders or graziers) travel long distances with ruminants, while others tend to livestock closer to home using especially managed pastures and the cultivation of particular crops for fodder. The social organization and traditions of pastoral communities have been the focus of anthropological inquiry since the 1950s (Dahl and Hjort 1980).More recently, anthropologists have sought to document the environmental and biological knowledge of pastoralists (Dong et al. 2016; Kardulias 2015). An implicit and highly interdisciplinary ‘‘ethnobiology of pastoralism’’ has now emerged which documents pastoral knowledge of medicinal and food plants, indicators of environmental and vegetation change, and local craft traditions which rely on organic materials (Beinart 2013; Darwish and Aburjai 2010; Fassio et al. 2014; French 2017; Magnani 2016). These studies highlight how pastoral local knowledge has the power to influence three key areas of policy, research, and development: landscape management, sustainable use of natural resources, and conservation and restoration of biological diversity. This special section on the Ethnobiology of Pastoralism calls attention to this emerging field of study and offers new insight into how pastoral local knowledge can contribute to the key challenges we face in the twenty-first century. These challenges include the rapid decline of biological diversity, increases in invasive plants, unsustainable and intensive livestock production systems, and the loss of pastoral ways of life due to enforced sedentarization programs. This brief introduction to the special section outlines the origins of pastoralism, the drivers of the decline of modern pastoralism, an overview of the papers in the issue, and key challenges facing the future of pastoralism into the twenty-first century.